The Effect of Discipline and Career Development on Organizational Citizenship Behavior (OCB) and Its Implications on Performance - Andrasita, Tara Amalia; Panjaitan, Saur (Universitas Pamulang, 2023)
This study aims to analyze and test whether there is influence of work discipline and career development on the performance of employees of PT. NOK Indonesia. Work discipline is an attitude of willingness and willingness of a person to obey and comply with the regulations that apply around him (Singodimedjo, 2002). Career development affects employee performance, where career development is a formal approach taken by the organization to ensure that employees with the right qualifications and experience are available when needed. This type of research is to use a quantitative research type, the population of NOK Indonesia employees and a sample of 83 employees. This study uses the Structural Equation Modeling (SEM) analysis model to determine how much independent influence the dependent variable has through the intervening variables, carried out using the Lisrel 8.8 program. The research results show that Discipline has no significant effect on Organizational Citizenship Behavior (OCB). Career development has a significant effect on Organizational Citizenship Behavior (OCB). Discipline has no significant effect on performance. Discipline has a significant effect on performance. Organizational Citizenship Behavior (OCB) has a significant effect on performance. Discipline and career development have a significant effect on Organizational Citizenship Behavior (OCB). Discipline and career development, and Organizational Citizenship Behavior (OCB) have a significant effect on performance. Discipline can improve performance both directly and indirectly. And career development can improve performance directly and indirectly through Organizational Citizenship Behavior (OCB).